AGGREGATION WITH A NON-CONVEX LABOR SUPPLY DECISION, UNOBSERVABLE EFFORT, AND INCENTIVE (“FAIR”) WAGES - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 9 No 2 (2018): TPREF, Volume IX, Issue 2(18), Winter 2018, 2018)
The purpose of this note is to explore the problem of a non-convex labor supply decision in an economy with unobservable e_ort and incentive ("fair") wages a la Danthine and Kurmann (2004), and explicitly perform the aggregation presented there without a formal proof, and thus provide - starting from micro-foundations - the derivation of the expected utility functions used for the aggregate household. We show how lotteries as in Rogerson (1988) can be used to convexify consumption sets, and aggregate over individual preferences. With a discrete labor supply decisions, the elasticity of aggregate labor supply becomes a function of effort